D-Dimer Is a Predictive Factor of Cancer Therapeutics-Related Cardiac Dysfunction in Patients Treated With Cardiotoxic Chemotherapy - Oikawa, Masayoshi; Yaegashi, Daiki; Yokokawa, Tetsuro; Misaka, Tomofumi; Sato, Takamasa; Kaneshiro, Takashi; Kobayashi, Atsushi; Yoshihisa, Akiomi; Nakazato, Kazuhiko; Ishida, Takafumi; Takeishi, Yasuchika (Frontiers in Cardiovascular Medicine, 2022)
Background: D-dimer is a sensitive biomarker for cancer-associated thrombosis, but little is known about its significance on cancer therapeutics-related cardiac dysfunction (CTRCD). Methods: Consecutive 169 patients planned for cardiotoxic chemotherapy were enrolled and followed up for 12 months. All patients underwent echocardiography and blood test at baseline, as well as at 3-month, 6-month, and 12-month. Results: The patients were divided into 2 groups based on the level of D-dimer (>1.65 µg/ml or ≦1.65 µg/ml) at baseline before chemotherapy: High D-dimer group (n=37) and low D-dimer group (n=132). Left ventricular ejection fraction (EF) decreased at 3-month and 6-month after chemotherapy in high D-dimer group (baseline, 65.2% [62.8%-71.4%]; 3-month, 62.9% [59.0%-67.7%]; 6-month, 63.1% [60.0%-67.1%]; 12-month, 63.3% [58.8%-66.0%], P=0.03), but no change was observed in low D-dimer group. The occurrence of CTRCD within the 12-month follow-up period was higher in the high D-dimer group than in the low D-dimer group (16.2% vs. 4.5%, P=0.0146). Multivariable logistic regression analysis revealed that high D-dimer level at baseline was an independent predictor of the development of CTRCD (odds ratio 3.93, 95% CI [1.00-15.82], P=0.047). Conclusion: We should pay more attention for elevated D-dimer level not only as a sign of cancer-associated thrombosis but also future occurrence of CTRCD.